Unearthing Urban Narratives. Towards a Repository of Methods: Working Group 3 - Milián Bernal, Dalia; Machado e Moura, Carlos (Writingplace, 2023)
Urban narratives offer a situated, experiential and subjective window into urban places. They come in spoken, visual and written forms and can be queried through a variety of approaches and methods. This contribution draws on the work of WG3–Methodological Framework of the COST Action–Writing Urban Places and reflects on the quest to find and bring together different methods and approaches to unearth, understand and retell urban narratives. We begin this essay by contextualizing the growing interest in narratives within the multidisciplinary field of urban studies and acknowledging the need for methods and approaches to find, analyse, represent and construct such narratives. Following this introduction, we briefly describe the task of WG3 and broadly present the range of methods that were collected as well as the interesting outputs that were produced, including a special issue in a journal, an interactive and iterative online platform, an international digital conference, a book with around 50 methods and assignments, and a set of postcards to disseminate them. Subsequently, we reflect on this process and discuss the way in which: it helped visualize the often hidden spaces/sites/places where narratives can be found; it unsettled our understanding of what constitutes an urban narrative as well as a method and what these methods are for; and it illustrated the potential of narratives as a medium not only to unlock and generate situated, subjective and experiential knowledge about urban places, but also to mobilize ideas that may even shape urban futures.